438 "How do you define Resilience?" Examining the Psychological Resilience of Black Adults Living with Sickle Cell Disease (SCD). (April 2022) - Conn, Corinne April Iolanda; Creary, Melissa; Bonham, Vence
Abstract : OBJECTIVES/GOALS: This study examines psychological resilience in adults living with Sickle Cell Disease (SCD) in the U.S. aiming to explore how psychological resilience is defined by this community. METHODS/STUDY POPULATION: Participants were recruited between 2014 – 2018, from across the U.S. as part of an ongoing cross-sectional study: Insights into Microbiome and Environmental Contributions to Sickle Cell Disease and Leg Ulcers Study (INSIGHTS). Inclusion criteria included age of 18 or older, with a clinical history of SCD, and were interviewed if they completed the Brief Resilience Scale (BRS) as part of INSIGHTS. 150 study participants were separated by their BRS scores into "High" and "Low" scoring quartiles. 30 participants were randomly selected, 15 from the lowest quartile and 15 from the highest. All participants completed the Connor Davidson Resilience (CD) measure at the end of their qualitative interview. All identified as Black with an average age of 42.5 (13 F, 17 M). RESULTS/ANTICIPATED RESULTS: Three main concepts emerged within both groups in response to the question "How do you define resilience?" (a) not giving up (b) how one deals with challenges and (c) moving forward. DISCUSSION/SIGNIFICANCE: Our analysis shows that the BRS may not be a precise or accurate indicator of the resilience of adults living with SCD. Therefore, it remains to be seen if these measures are descriptive of these individuals true psychological or physiological state as they have not been used in this community until now.